Dedication: Eugene David Cruz-Uribe, Ph.D. December 22, 1952–March 12, 2018 - Piccione, Peter.
This volume of the Journal of the American Research Center in Egypt is dedicated to the memory of Prof. Eugene D. Cruz-Uribe, who served as its editor from 2008 until his sudden and unexpected death in March. He was born and raised in Green Bay, Wisconsin and, since 2013, he lived in Richmond, Indiana, where he served on the faculty of Indiana University East. Although he retired in 2017, he maintained an active schedule of research and travel to Egypt, as well as his fulfilling his responsibilities with this journal.